Standardization of Simulated patients: Assessing their efficiency and evaluating their Perception - Heethal Jaiprakash, HMP Singh, Jaiprakash Mohanraj, Veena Joshi, Siva Achanna, Ravindran Jegasothy (International Journal of Advanced Science and Technology, 2020)
Changes in healthcare delivery and concernsabout the lack of standardization of clinical examinations lead to the introduction of the ‘simulated patient’ (SP).This study aims at the standardization of simulated patients and assessing their efficiency and evaluating their perception.This was an observational study with a total of nine participants.The standardization was done for diseases of three different specialties in history taking and examination.It was a one day workshop that consisted of lectures and hands-on training.The participants were made to simulate the condition as per their understanding in the workshop, and that was recorded twice, one on the day of the workshop and another few weeks later and these videos were assessed by four subject experts on a later date. The perception of the participants on the workshop was recorded using a five-point Likert scale, and evaluation was done using a rubric. Data were analyzed using descriptive statistics.A study had six males and three females. The mean age of the participants was 62.2±9.5years. The participants had a positive response to the workshop and the mean scores for the questions were between4.2 and4.8. The assessment of the videos by the assessors on the day of the workshop shows that the SP who simulated angina who had a mean score of 43 did the best followed by hemiplegia who had a score of 42.The SPs had a positive perception of the workshop. The SPs who mimickedangina,hemiplegia and DUB performed the best when assessed by experts.